ChemInform Abstract: 9‐Fluorenylmethyl (Fm) Disulfides: Biomimetic Precursors for Persulfides. Issue 29 (June 2016) - Park, Chung‐Min; Johnson, Brett A.; Duan, Jicheng; Park, Jeong‐Jin; Day, Jacob J.; Gang, David; Qian, Wei‐Jun; Xian, Ming
Abstract: The title disulfides can convert the small molecules and protein thiols to disulfides which can further generate highly reactive persulfides in their anionic forms.